EVALUASI PROGRAM SCHOOL OF MASTER TEACHER SEKOLAH GURU INDONESIA DOMPET DHUAFA WILAYAH KABUPATEN BEKASI - Rachmawati Rachmawati (Jurnal Kinerja, 2023)
This study aims to evaluate the training program of the school of master teachers in Indonesian teachers’ schools of the poor. School of master teacher program is one of the intensive Indonesian teachers school programs and aims to form teachers who have the spirit of educators, teachers and leaders.This non-formal training program, which I under the auspices of the Dhuafa Wallet Education Network, is held once a week for three months. This study uses qualitative research by selecting case studies in the implementation of the school of master teacher program in the Indonesian teacher school district of Bekasi. The results of the research show that the School of Master Teacher (SMT) is one of the Indonesian Teacher School programs that focuses on increasing teacher competency to become teachers who are educators, educators and have social leadership. The implementation of the SMT program in general has been good, but of course it cannot be separated from the other side that there are still various shortcomings that still need to be corrected in several aspects so that it can provide wider and much better benefits in the coming period.